State-of-the-art in the search engine optimisation world. (3rd February 2023) - Chen, Jun-Cheng
Search engine optimisation (SEO) has become a popular digital marketing technique in recent years but there is a paucity of efforts in the academic world. Due to the lack of research, this study aims at reviewing the previous studies in order to provide the future analysis as a foundation. This paper employs secondary research to collect the existing scholarship and to offer an intelligible overview of SEO and its related state-of-the-art knowledge. This is a review-type paper that gives you the evolution and perspectives of digital marketing, and search engine marketing, including SEO and search engine advertising (SEA), also, the impact of SEO efforts on the performance of websites, business, and brand equity. The results can provide future researchers a clearer path to continue, and practitioners to follow suit for effective SEO decision-making.